Blockchain-based security in smart grid network. (6th May 2022) - Mishra, Shailendra
The cybersecurity threats in the smart grid network are prominent with conventional approaches providing integrated security control and communication protection for smart grids that are vulnerable to some types of attacks and limit their use in real-time applications. In this study, the statistical function predicts the system performance of the future timestamp and compares it with the actual performance to detect the attack. The asymmetric encryption function is used to find the user authentication, which is complex and increases the network latency. In this paper, a blockchain-based methodology is proposed for cybersecurity threat detection in smart grid networks without increasing the network latency. The proposed model is based on blockchain-based secure user authentication, lightweight data encryption and quantum key distribution multi-constraint-based edge selection, bi-fold intrusion detection system, and optimal user privacy management. The results show that the accuracy of the proposed model is 98%.